Diagnostic of the systems of transportation of solids in sugar factories of Villa Clara - Pérez Castellanos, Eusebio; Hernández Ortega, Robert; Espinosa Acevedo, Andrés (Centro Azúcar Journal, 2011)
Presently work offers the results of a diagnosis carried out to the system of conveying of solids in the sugar companies of Villa Clara in order to determine the efficiency of operation of such equipment. A characterization of each conveyor about the geometric and kinematics characteristics is developed. The methodical of calculus of the conveyors in Excel is used. In the work was established that all the equipments are oversized. These conditions make inefficient the system in the technological and energetic features.